From development to clinical success: the journey of established and next-generation BTK inhibitors - Gupta S.; Sharma A.; Shukla A.; Mishra A.; Singh A. (My University, 2025)
Over the past decade, Bruton’s tyrosine kinase (BTK) has emerged as a pivotal therapeutic target for B-cell malignancies and autoimmune diseases, given its essential role in B-cell development and function. Dysregulation of BTK signalling is implicated in a range of hematologic cancers, including Waldenström’s macroglobulinaemia (WM), mantle cell lymphoma (MCL), and chronic lymphocytic leukaemia (CLL). The development of BTK inhibitors (BTKIs), starting with ibrutinib, has revolutionized the treatment of these malignancies by inhibiting B-cell receptor (BCR) signalling and inducing apoptosis in malignant B-cells. Despite the impressive clinical efficacy of ibrutinib, challenges such as resistance mutations and off-target effects remain. To address these issues, next-generation BTKIs, including acalabrutinib, orelabrutinib, zanubrutinib, and pirtobrutinib, have been developed, offering improved specificity and reduced toxicity profiles. This review highlights the therapeutic potential of BTK-targeted therapies in treating B-cell malignancies, discusses recent advancements with FDA-approved BTKIs, and explores the latest clinical outcomes from ongoing trials of novel inhibitors. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2025.